Teachers' training in exploiting 3D virtual worlds for teaching and learning - Sampson, Demetrios; Kallonis, P. (Springer New York, 2012)
© 2012 Springer Science+Business Media, LLC. All rights reserved. Today, the emergence of technologies, such as 3D Virtual Worlds, which provide realistic three-dimensional environments and offer engaging, interactive and immersive experiences, creates new opportunities for teaching and learning. However, the possible use of 3D Virtual Worlds remains a major challenge for teachers and trainers, since these environments introduce new concepts with which even teachers and trainers who are experienced and keen on using digital technologies are not familiar. This problem has been identified by the research and the educational community. To this end, there are research studies that have raised issues, such as, the extra pressure applied to teachers who teach within 3D Virtual Worlds, and the lack of understanding for the new opportunities offered by 3D Virtual Worlds in teaching and learning. Within this context, in this study we present a module for Teachers' Continuing Professional Development designed using the instructional strategy Synectics Making the strange familiar, aiming towards acquiring appropriate competences for teaching and for developing innovative educational practices within 3D Virtual Worlds.